Active antimicrobial substances of cherry leaf extracts (Muntingia calabura L.) against Methicillin-Resistant Staphylococcus aureus (MRSA) based on GC-MS analysis - Nanik Sulistyani; Mika Triza Misba; Nurkhasanah Nurkhasanah (Universitas Ahmad Dahlan, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the bacteria that triggers nosocomial diseases. Bacterial resistance requires continuous exploration of active antimicrobial substances from various sources, including medicinal plants. Leaves of cherry (Muntingia calabura L.) reportedly contain three classes of compounds, namely, tannins, flavonoids, and saponins. This research was designed to identify active antimicrobial substances in cherry leaves that could inhibit the growth of MRSA. It employed the Kirby-Bauer test to examine the antimicrobial activities of the leaf extracts of Muntingia calabura L. (EMC) against MRSA. Through GC-MS, active substances were detected from the presence of active spots on TLC plates, as determined by direct-contact bioautography. The TLC used silica gel F254 as the stationary phase and chloroform:ethyl acetate (9:1) as the mobile phase. The antimicrobial activity test results showed that the zone of inhibition of 10% w/v EMC was 10.91±0.75 mm in diameter. At 5% w/v and 2.5% w/v, EMC created zones of inhibition with diameters of 8.5±0.25 mm and 7.25±0.25 mm, respectively. Meanwhile, at 1.25% w/v, it showed no inhibitory activities. Based on the TLC-Bioautography profile, the active spot that produced zones of inhibition was located at Rf 0.04 mm. The GC-MS analysis of this spot detected the presence of two compounds: the first compound had a similarity index of 35% with 3,11,13-triacetycynaratriol, and the second one had a similarity index of 80% with hexaborane-12. Cynaratriol is known to posses antimicrobial activity, whereas hexaborane is the opposite. In conclusion, the minimum inhibitory concentration of EMC for MRSA is 2.5% w/v. Also, the active compounds of EMC bear 35% similarities to 3,11,13-triacetycynaratriol.